Analisis Pendistribusian Produk pada UKM DO’A IBU dengan Metode Minimum Spanning Tree - Aldi Pratama; Wahyudin Wahyudin; Dene Herwanto; Shakty Adhea Aditya (Peneliti.net, 2022)
Supply Chain Management has a very important role both in achieving a more effective integration of suppliers, manufacturers, distributors, retailers and customers, so that they can produce goods on time, quantity, and place in order to achieve minimum costs of the entire system. UKM Macaroni and Crackers DO'A IBU is a business that was founded in 2003 and is still operating today by engaging in the cracker-type snack industry at an economical price. The distribution of goods is carried out directly to the marketing area. One method that can be used to optimize the distribution path is the minimum spanning tree method, Prim's algorithm and Kruskal's algorithm. Minimum Spanning Tree (MST) can minimize costs by optimizing distance. The object of study in this research is the product distribution route for Macaroni SMEs and DO'A IBU Crackers. After doing manual data processing and using POM QM software, the final result is the same, namely the distribution distance of 27.2 Km. These results indicate that there is a reduction in mileage as far as 9.6 Km which was originally 36.8 Km. From optimizing the mileage, it is expected to reduce the cost and time required.